Association of tuberculosis and tricuspid valve endocarditis in AIDS patient with Ebstein heart anomaly - Radovanović Spurnić, Aleksandra; Vujisić Tešić, Bosiljka; Boričić Kostić, Marija; Jevtović, Djordje (The Journal of Infection in Developing Countries, 2018)
A case of tricuspid valve endocarditis in an AIDS patient, an intravenous drug user, initially empirically unsuccessfully treated as a Staphylococcus aureus infection, and thereafter turned to be, most likely, of Mycobacterium tuberculosis etiology is presented.